Social phobia in obsessive-compulsive disorder: Prevalence and correlates - Assuncao, Melissa Chagas [UNESP]; da Conceicao Costa, Daniel Lucas; de Mathis, Maria Alice; Shavitt, Roseli Gedanke; Ferrao, Ygor Arzeno; do Rosario, Maria Conceicao; Miguel, Euripedes Constantino; Torres, Albina Rodrigues [UNESP] (Elsevier B.V., 2012)
Background: Social Phobia (SP) is an anxiety disorder that frequently co-occurs with obsessive-compulsive disorder (OCD); however, studies that evaluate clinical factors associated with this specific comorbidity are rare. The aim was to estimate the prevalence of SP in a large multicenter sample of OCD patients and compare the characteristics of individuals with and without SP.Method: A cross-sectional study with 1001 patients of the Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders using several assessment instruments, including the Dimensional Yale-Brown Obsessive-Compulsive Scale and the Structured Clinical Interview for DSM-IV Axis I Disorders. Univariate analyses were followed by logistic regression. Results: Lifetime prevalence of SP was 34.6% (N=346). The following variables remained associated with SP comorbidity after logistic regression: male sex, lower socioeconomic status, body dysmorphic disorder, specific phobia, dysthymia, generalized anxiety disorder, agoraphobia, Tourette syndrome and binge eating disorder.Limitations: The cross-sectional design does not permit the inference of causal relationships; some retrospective information may have been subject to recall bias; all patients were being treated in tertiary services, therefore generalization of the results to other samples of OCD sufferers should be cautious. Despite the large sample size, some hypotheses may not have been confirmed due to the small number of cases with these characteristics (type 2 error). Conclusion: SP is frequent among OCD patients and co-occurs with other disorders that have common phenomenological features. These findings have important implications for clinical practice, indicating the need for broader treatment approaches for individuals with this profile. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Obsessive-compulsive disorder; Social phobia; Social anxiety disorder; Comorbidity; Phenotypic characteristics; Phenomenology